2021
DOI: 10.7150/jca.47112
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0000700 promotes cell proliferation and migration in Esophageal Squamous Cell Carcinoma by sponging miR-1229

Abstract: Accumulating evidence has demonstrated that circular RNAs (circRNAs) are involved in the pathogenesis of cancer, including that of esophageal squamous cell carcinoma (ESCC). The current study aimed to investigate the role of hsa_circ_0000700 in ESCC. hsa_circ_0000700, miR-1229, and related functional gene expression was measured by RT-qPCR. To characterize the functions of hsa_circ_0000700 and miR-1229, ESCC cells were infected with hsa_circ_0000700-specific siRNA, miR-1229 mimics, and an inhibitor alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“… 22 Moreover, the proliferative and migratory capacities of ESCC cells were decreased and apoptosis was increased by hsa_circ_0000700 knockdown. 23 In this study, a novel upregulated circRNA named circ_0005231 was identified based on the GEO database, and we further confirmed the level of circ_0005231 was remarkably upregulated in ESCC plasma, tissues and cells. Next, we knocked down circ_0005231 expression and evaluated the effects on ESCC cell behavior.…”
Section: Discussionsupporting
confidence: 67%
“… 22 Moreover, the proliferative and migratory capacities of ESCC cells were decreased and apoptosis was increased by hsa_circ_0000700 knockdown. 23 In this study, a novel upregulated circRNA named circ_0005231 was identified based on the GEO database, and we further confirmed the level of circ_0005231 was remarkably upregulated in ESCC plasma, tissues and cells. Next, we knocked down circ_0005231 expression and evaluated the effects on ESCC cell behavior.…”
Section: Discussionsupporting
confidence: 67%
“…Wang et al [7] revealed that the downexpression of PSMB5 significantly inhibited the proliferation and migration of breast cancer cells both in vitro and in vivo. Fang et al [13] demonstrated that hsa_circ_0000700 could activate PSMB5 indirectly to enhance esophageal squamous cell carcinoma proliferation. These findings suggest an oncogenic role of PSMB5, which is consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor‐promoting role of PSMB5 has been reported in relation to many human cancers, such as breast cancer, esophageal squamous cell carcinoma and prostate cancer. Aberrant expression of PSMB5 is correlated to tumor cell proliferation metastasis and drug resistance [ 7 , 11 , 12 , 13 , 14 ]. However, as for a subunit of the whole proteasome complex, the functional role and biological mechanism of PSMB5 in HCC still remain largely unknown.…”
mentioning
confidence: 99%
“…For RNase R treatment, the total RNA of 2 μg was extracted from AC16 cells and incubated with or without 3 U/μg of RNase R (Epicentre) for 15 min at 37°C. Circ_0040414 and Linear 0040414 level was quantified using RT-qPCR (Fang et al, 2021).…”
Section: Actinomycin D and Rnase R Assaymentioning
confidence: 99%